Flexor digitorum accessorius causing tarsal tunnel syndrome in a paediatric patient: A case report and review of the literature. Issue 2 (June 2015) - Molloy, A.P.; Lyons, R.; Bergin, D.; Kearns, S.R.
Highlights Anatomy of FDA. Unusual anatomical variant. Tarsal tunnel syndrome. MRI imaging. Intraoperative pictures.